A randomized trial of artemether-lumefantrine and dihydroartemisinin-piperaquine in the treatment of uncomplicated malaria among children in western Kenya - Agarwal, Aarti (BioMed Central, 2013)
BACKGROUND: Artemether-lumefantrine (AL) was adopted as first-line treatment for uncomplicated malaria in Kenya in 2006. Monitoring drug efficacy at regular intervals is essential to prevent unnecessary morbidity and mortality. The efficacy of AL and dihydroartemisinin-piperaquine (DP) were evaluated for the treatment of uncomplicated malaria in children aged six to 59 months in western Kenya. METHODS: From October 2010 to August 2011, children with fever or history of fever with uncomplicated Plasmodium falciparum mono-infection were enrolled in an in vivo efficacy trial in accordance with World Health Organization (WHO) guidelines. The children were randomized to treatment with a three-day course of AL or DP and efficacy outcomes were measured at 28 and 42 days after treatment initiation. RESULTS: A total of 137 children were enrolled in each treatment arm. There were no early treatment failures and all children except one had cleared parasites by day 3. Polymerase chain reaction (PCR)-uncorrected adequate clinical and parasitological response rate (ACPR) was 61% in the AL arm and 83% in the DP arm at day 28 (p = 0.001). PCR-corrected ACPR at day 28 was 97% in the AL group and 99% in the DP group, and it was 96% in both arms at day 42. CONCLUSIONS: AL and DP remain efficacious for the treatment of uncomplicated malaria among children in western Kenya. The longer half-life of piperaquine relative to lumefantrine may provide a prophylactic effect, accounting for the lower rate of re-infection in the first 28 days after treatment in the DP arm.